Influence of ionic and non-ionic radiographic contrast media on leukocyte adhesion molecules - Guy L. J. Vermeiren; Roel Willems; Marc J. Claeys; Chris Vrints; Herman Slegers; Philippe G. Jorens (Mediators of Inflammation)
Background: Many papers have focused on the importance of granulocytes in the process of reperfusion and ischemia. Most of the clinical studies measured several parameters of this process during and after coronary angiography, without taking into account the effect of the radiographic contrast media (RCM) used during this procedure.